أهمية المقاصد وأثرها في استنباط الأحكام - سحنون عمارية; يزير نوال (جامعة عمار ثليجي الاغواط, 2023)
علم مقاصد الشرعية هو علم عظيم الأثر جليل القدر، فهو ميدان التفاعل المثمر بين النصوص الخالدة والوقائع المتجددة في أل تناهي النصوص وعدم تناهي الحوادث، وهذا ما يفتح وجهات متطورة للاجتهاد، فماهي أهمية علم المقاصد الشرعيةlaw) is a highly influential and significant field. It represents the fruitful interaction between timeless texts and evolving circumstances, as texts remain fixed while events continuously change. This opens up advanced avenues for Ijtihad (independent legal reasoning). So what is Maqasid Al-Sharia science and to what extent can it be invested for Ijtihad and justification? This study adopts descriptive analytical method to highlight the importance and juristic impact of working within the framework of Maqasid Al-Sharia. The most important results of the study indicate that Maqasid Al-Sharia greatly contributes to empowering jurists with a profound revolution. It helps them understand the religious texts and deduce appropriate legal verdicts. It also helps resolve conflicts between texts and prioritize evidence. As وما مدى استثمارها في الاجتهاد والتعليل؟ ول جابة على هذه الإشكالية جاءت هذه الد ا رسة متبعتا المنهج الوصفي التحليلي، بهدف إب ا رز هذه الأهمية والأثر الفقهي للعمل المقاصدي. أما أهم نتائجها: أنا المقاصد الشرعية تساهم بشكل كبير في إمداد المجتهد بثورة عظيمة فتساعده في فهم النصوص الشرعية واستنباط الأحكام الشرعية المناسبة، وإ ا زلة التعارض بين النصوص والترجيح بين الأدلة، أما التعليل فهو ما يعتمد عليه المجتهد لاستنباط الأحكام.